2017
DOI: 10.3130/jaabe.16.565
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban and Building Form and Microclimate on the Energy Consumption of Buildings - Based on Statistical Analysis-

Abstract: This study investigates certain correlations between the impacts of urban and building form and microclimate on the energy consumption of buildings. It applies microscopic elements such as urban form and tissue, building form and character, and microclimate as factors in the energy consumption of buildings. To this end, the energy consumption of selected buildings in Seoul in August of 2014 was analyzed. Based on microscopic elements within a radius of 500 meters of 23 Automated Weather Station (AWS) measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Even if more than one indicator analysed, no study has examined the effect of urban built form at the same time with density and energy holistically. It is crucial to give information about urban built form as it alters the microclimatic conditions (Emmanuel and Steemers, 2018) that consequently affect building energy consumptions (Lee and Jeong, 2017). There seems to be a lack of a unified set of guidelines to communicate urban density indicators and their relationships with urban built forms.…”
mentioning
confidence: 99%
“…Even if more than one indicator analysed, no study has examined the effect of urban built form at the same time with density and energy holistically. It is crucial to give information about urban built form as it alters the microclimatic conditions (Emmanuel and Steemers, 2018) that consequently affect building energy consumptions (Lee and Jeong, 2017). There seems to be a lack of a unified set of guidelines to communicate urban density indicators and their relationships with urban built forms.…”
mentioning
confidence: 99%
“…In addition, climate-responsive designs also have an impact on energy-efficient uses. The characteristics, as well as the form and the pattern of buildings or cities may influence the formation of microclimates, resulting in energy consumption changes (Lee, 2017). For building as an example, it occurs because the design of the building's inner space conditions also affects the energy use in the building, based on the microclimate response (Alwetaishi, 2016;Strelková, 2013;Pisello, 2015).…”
Section: Snapshoot Of Literature Reviewmentioning
confidence: 99%
“…Besides the physical condition of a building, such as the building type [ 5 ], construction [ 6 ], and HVAC (Heating, Ventilation and Air Conditioning) system [ 7 ], and its energy consumption patterns (ECP) [ 8 , 9 ], such as energy-use behavior and lifestyles, numerous studies have observed that the surrounding environment is critical in influencing the building heating energy consumption ( Figure 1 ) [ 10 , 11 , 12 ]. Urban morphology and climatic conditions have been identified as key environmental factors that affect the overall heating demand in cities [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Martins et al [ 14 ] observed that aspect ratio and building height accounted for almost 50% of the overall impact on heating demand. Furthermore, floor area ratio and shape factor are also energy-related urban morphological parameters [ 11 , 17 ]. The impact of climatic conditions has been widely discussed as well.…”
Section: Introductionmentioning
confidence: 99%